Studies on Optimization of Growth Parameters for Enhanced Production of Antibiotic Alkaloids by Isolated Marine Actinomycetes - Nagaseshu Pudi, Gayatri Devi Varikuti, Anil Kumar Badana, Murali Mohan Gavara, Seema Kumari, Ramarao Malla (Journal of Applied Pharmaceutical Science, 2016)
The aim of the present study is to optimize the growth conditions for improved production of alkaloids by promising marine actinomycetes isolated from marine sediments collected on Kakinada coast. The bioactive compounds were extracted from the isolated actinomycete using organic solvents and screened for alkaloids using qualitative tests. The presence of alkaloids in the crude methanol extract was confirmed by UV spectroscopic analysis and quantified by BCG method. The effect of pH, temperature, carbon and nitrogen sources on the growth and fermentative production of alkaloids was optimized. The strain was improved for enhanced production of alkaloids by physical and chemical mutagenesis. The antimicrobial activity of the crude alkaloid extract was determined by the well diffusion method. The isolated strain exhibited the highest growth and alkaloid production at pH 6 and temperature 30oC in 7 days. The alkaloid production was significantly increased 4.5-folds with UV treatment for 30 min and further, 5.5-folds with ethidium bromide treatment(30µg/mL) for 1hr. The resultant double mutant strain exhibited significantly high antimicrobial activity against S. aureus compared to other bacterial strains with MIC index less than 4. The isolated double mutant strain of actinomycetes can be a potential source of antibiotic alkaloids.
Keywords: Actinomycetes, optimization, strain improvement, antimicrobial activity, alkaloids.